The 100 m Composite Ship? - Michael John Lowde; Henry George Arthur Peters; Ruadan Geraghty; Jasper Graham-Jones; Richard Pemberton; John Summerscales (Journal of Marine Science and Engineering, 2022)
Fibre-reinforced polymer (FRP) matrix composites are widely used in large marine structures, and in wind turbines where blade lengths are now over 100 m. Composites are the material of choice for small vessels due to ease of manufacture, high hull girder stiffness, buckling resistance, corrosion resistance and underwater shock resistance. Ships over 100 m are still built using traditional steel and/or aluminium, but so far not FRP. Composite ship lengths have increased over the past 50 years, but fundamental technical challenges remain for the 100 m composite ship. Preliminary studies suggest a possible 30% saving in structural weight, a 7–21% reduction in full load displacement, and a cost saving of 15%. However, economic considerations, design codes, manufacturing limits, safety and end of life scenarios need to be addressed before a 100 m ship is built. Innovative materials and structures, notably carbon fibre composite skinned sandwich construction, or aramid fibres with vinylester modified epoxy resin, should result in increased mechanical performance and consequent improvements in economics and manufacturing processes. A linear extrapolation of length vs. launch dates predicts the first 100 m ship would be launched in 2042.